The Discourse on the New Class and its Impact on the Debates about the Role of Intellectuals in Post-Socialist Countries - Gečienė, Irmina (Sociologija. Mintis ir veiksmas, 2003)
In this paper will be presented the main arguments of the New Class theories as well as some relevant critics and further elaboration of issue that appeared in later discourse on Western intellectuals mainly by theoretical assumptions in Jacoby and Lash works. And the last part of paper will be devoted to the fruitful use of this approach in works of well known researches of post-communist transformation such as I. Szelenyi and G. Konrad in Hungary, M. Kempny, J. Kurczewska and E.Mokrzycki in Poland, I.Bernik in Slovenia and L. Donskis in Lithuania, L. Greenfeld and L. Gudkov in Russia.